2020
DOI: 10.1016/j.amsu.2020.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV status and predictors of successful treatment outcomes among tuberculosis patients: A six-year retrospective cohort study

Abstract: Tuberculosis (TB) remains a major global public health problem. Hence, the study aimed to assess the impact of human immune virus (HIV) status and predictors of successful treatment outcomes of TB patients enrolled at Nekemte specialized hospital. An institution-based retrospective cohort study was conducted and the data analyzed using SPSS version 24.0. A multivariable logistic regression model was fitted to identify the association between treatment outcome and potential predictor variables. The association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(181 reference statements)
2
9
0
Order By: Relevance
“…Analysis of the study data demonstrated that the TB/HIV co-infected patients had poor treatment outcomes with a success rate of only 57.1%, which is lower than the WHO target set for MDG (85%) and far lower to End TB Strategy success rate for 2025 (≥ 90.0%) (WHO, 2019). These results are almost similar to the study of 26,168 TB cases notified in Malaysia in 2017, 56.0% (WHO, 2018a), TB/HIV co-infected patients in the Klang Valley, 53.4% (Ismail & Bulgiba, 2013) and of TB patients enrolled at Nekemte Specialized Hospital, Western Ethiopia, 58.06% (Fekadu et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of the study data demonstrated that the TB/HIV co-infected patients had poor treatment outcomes with a success rate of only 57.1%, which is lower than the WHO target set for MDG (85%) and far lower to End TB Strategy success rate for 2025 (≥ 90.0%) (WHO, 2019). These results are almost similar to the study of 26,168 TB cases notified in Malaysia in 2017, 56.0% (WHO, 2018a), TB/HIV co-infected patients in the Klang Valley, 53.4% (Ismail & Bulgiba, 2013) and of TB patients enrolled at Nekemte Specialized Hospital, Western Ethiopia, 58.06% (Fekadu et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, pulmonary TB anatomy comprised most cases, 58.7% (168 out of 286) in the unsuccessful and 68.2% (260 out of 381) in the successful group. It contradicted the study done by others among TB patients (Fekadu et al, 2020;Tok et al, 2020). The presentations with pulmonary TB were often late resulting in poor treatment outcomes and increased risk of delay to start the treatment.…”
Section: Discussionmentioning
confidence: 83%
“…The two groups were significantly different in the distribution of CD4 count, 563 [465-702.5 cells/mm3] vs 345 [157-483 cell/ mm3] in HIV negative vs HIV positive respectively p = <0.001. Post stimulation, the expression of IL-6 in HIV negative TB patients was significantly higher than in the HIV positive 16,757366 [8,,686 pg/ml] vs. 9,508 [5,,008 pg/ml], respectively; p = 0.0360. TNF-α and IFN-γ were highly expressed in HIV negative TB patients compared to the HIV positive though not statistically significant.…”
Section: Resultsmentioning
confidence: 89%
“…We only observed higher expression of IL-6 in HIV negative patients in comparison to the HIV positive when stratified by level of CD4 counts as < 500 and � 500 cell/mm 3 for both cohorts. 21,953 [8,206 pg/ml] vs 9,505 [5,,313 pg/ml], p value = 0.0585 in patients with CD4 count < 500 cell/mm 3 and 13,168 [7,087-22,584 pg/ml] vs 10,413 [7,397-14,806 pg/ml], p value = 0.3744 for patients with CD4 count of � 500 cell/mm3 respectively. We found a positive pairwise correlation between TNF-α -alpha and IL-6 in both HIV positive and HIV negative patients, r = 0.61…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation